The exegetical and the ethical the Bible and the academy in the public square: essays for the occasion of Professor John Barton's 70th birthday - Barton, John 1948-; Clifford, Hywel 1973-; Daffern, Megan 1980- (Leiden Boston Brill, 2022)
Exegesis has ethical dimensions. This is the case for the Bible, which has a foundational status in traditional perspectives that is simultaneously contested in the modern world. This innovative essay collection, largely about Hebrew Bible/Old Testament texts, is written by an international team - all Doktorkinder of a pioneer in this area, Professor John Barton, whose 70th birthday this volume celebrates. With interdisciplinary angles, the essays highlight the roles and responsibilities of the biblical scholar, often located professionally between religious and secular domains. This reflects a broader reality: all readers of texts are engaged ethically in the public square of ideas
Contents -- Abbreviations -- Notes on Contributors XV -- Introduction -- Hywel Clifford and Megan Daffern -- Part 1: Establishing the Exegetical and the Ethical -- 1 The Basis of the Exegetical and the Ethical: What Is the Biblical Text? -- Alma Brodersen -- 2 Prophecy and the United Monarchy: The Origins of Exegesis in Prophetic Imitation -- James E. Patrick -- 3 How to Do Things with Scrolls: Writing and Ritual in Jeremiah 36 -- Laura Quick -- 4 Scepticism within the Academy: Questioning the History of Israel -- Katharine Dell -- Part 2: Enabling the Exegetical and the Ethical -- 5 The Riddle Minor Genre in the Old Testament: Clarity and Obscurity -- Aulikki Nahkola -- 6 Keeping Company in the Psalms: Ethics and Exegesis -- Megan Daffern -- 7 Ethics in Song of Songs -- Anselm C. Hagedorn -- 8 Yahweh as the Direction of Reference in Ezekiel's Oracles Against the Nations -- Andrew P. Langley -- 9 The Typological Interpretation of Scriptural Quotations in the New Testament: A Test Case for the Bible in the Academy -- Benjamin Sargent -- Part 3: Enacting the Exegetical and the Ethical -- 10 From Exclusion to Inclusion? Deuteronomy 23:1-8 in Philo and Beyond -- Hywel Clifford -- 11 Is There an Ethical Way to Read Genocidal Commands in "Holy Writ"? -- Christian Hofreiter -- 12 The Wisdom of Jonah: Biblical Interpretation in Late Antiquity -- Kris Sonek -- 13 A Tale of Two "Houses": The Scandals of Hereditary Succession and Super-Mega-Church Construction in Korea, and Old Testament Ethics -- S. Min Chun -- Conclusion -- John Barton -- Index.
Literaturangaben
Keywords: Bible -- Criticism, interpretation, etc; Ethics in the Bible; Festschrift